SISTEM INFORMASI AKUNTANSI LAPORAN KEUANGAN BERBASIS SAK EMKM PADA UD FATAR - Isnu Isnu; Agus Dwi Atmoko (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2022)
UD Fatar is one of the companies engaged in industry or manufacturing that produces crispy mushrooms. Accounting records at UD Fatar are still very simple and manual, namely recording cash in, cash out, and accounts receivable. UD Fatar has not depreciated assets, this is due to a lack of knowledge about how to prepare financial statements. So that the company's financial information becomes inaccurate. The research method in this study uses qualitative and quantitative data, namely conducting interviews, observations, documentation, and literature. Researchers do the preparation of financial statements UD Fatar using the Microsoft Excel 2010 application. This application is designed to be able to make financial reports automatically. The resulting report is the balance sheet, income statement, and notes to the financial statements as of January 31, 2018 in accordance with the accounting principles based on Financial Accounting Standards for Micro, Small, and Medium Enterprises. The results of this final project report are in the form of financial statements on UD Fatar with Microsoft Excel 2010 applications. Financial statements are made to find information about the balance sheet and income statement so that it can be used as a means of decision making in the future. While the application is used so that the process is faster and more accurate in preparing financial statements.